Remixing the tech: the digital media ecologies of the hip-hop artists from Grahamstown, South Africa - Schoon, Alette Jeanne (Centre for Film and Media Studies, 2018)
This ethnographic study describes the digital media ecologies of hip-hop artists in the marginalised township spaces of a town in South Africa. It shows how technology appropriation here is highly contextual and linked to social context, while simultaneously informed by limited digital infrastructure that characterises marginalised communities in the Global South. In describing their social context, the study situates these young people in a post-apartheid space of entrenched racialised inequality, where unemployed black youth have very few economic prospects. Here hip-hop offers protection against despair as it allows a young person to claim a dignified sense of self, which is partly constituted through digital media competency. Through the Black Consciousness philosophy, hip-hop artists in Grahamstown become highly critical of self-defeating narratives rooted in racism, colonialism and apartheid, which often manifest in violent forms of urban masculinity. Instead they find ways to "remix" their identities by incorporating alternative notions of a successful self. These new identities foreground agency and competency, and are informed both by knowledge of African tradition and language, and newly acquired competency in entrepreneurship, artistic genres and digital skills. The study argues that acquisition of digital skills in this space is best conceptualised through the community of practice approach, where skills development is social and linked to a sense of belonging and progress. Just as the hip-hop artists claim agency in remixing their notion of self, they also claim agency in remixing the limited digital technology available to them into various assemblages, so crafting innovative solutions to the constraints of limited and expensive digital infrastructure. Here, through a hip-hop culture that champions overcoming adversity, dysfunctional digital technology is constantly repaired and remixed. Hitherto, research on digital media use in the Global South has predominantly focused on the mobile phone in isolation. This study instead argues for the merits of a holistic digital ethnography, since observations of how these young people combine technologies such as mobile phones, computers and DVD players in everyday life, illustrate how innovation in marginalised spaces may be focused around the remixing of technology.